2002
DOI: 10.1023/a:1014814924965
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Carbamazepine (CBZ) has been extensively used in the treatment of epilepsy, as well as in the treatment of neuropathic pain and affective disorders. However, the mechanisms of action of this drug are not completely elucidated and are still a matter of debate. Since CBZ is not very effective in some epileptic patients and may cause several adverse effects, several antiepileptic drugs have been developed by structural variation of CBZ, such as oxcarbazepine (OXC), which is used in the treatment of epilepsy since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(55 citation statements)
references
References 89 publications
0
53
0
2
Order By: Relevance
“…Carbamazepine and its derivative oxcarbazepine inhibit voltage-gated sodium channels and potentiate GABAergic neurotransmission [22, 23]. In addition to the above-mentioned Cochrane review showing some evidence in support of carbamazepine for treating withdrawal, perhaps with some advantages over benzodiazepines, Barrons and Roberts [24] recently completed a systematic review of carbamazepine and oxcarbazepine for the treatment of AWS which also lends support.…”
Section: Non-benzodiazepine Anticonvulsants (Nbacs) For the Treatmementioning
confidence: 99%
See 1 more Smart Citation
“…Carbamazepine and its derivative oxcarbazepine inhibit voltage-gated sodium channels and potentiate GABAergic neurotransmission [22, 23]. In addition to the above-mentioned Cochrane review showing some evidence in support of carbamazepine for treating withdrawal, perhaps with some advantages over benzodiazepines, Barrons and Roberts [24] recently completed a systematic review of carbamazepine and oxcarbazepine for the treatment of AWS which also lends support.…”
Section: Non-benzodiazepine Anticonvulsants (Nbacs) For the Treatmementioning
confidence: 99%
“…Four (one out-patient and three inpatient) studies compared carbamazepine to benzodiazepines for the treatment of AWS [25, 27, 29, 30]. No significant differences were found on seizure incidence and DTs, although there was significant heterogeneity, and as most of the studies were designed to examine withdrawal symptoms (i.e., CIWA-Ar scores), they were underpowered to assess carbamazepine's role in the reduction of seizures and DTs [22]. One of the more promising studies of carbamazepine treatment of AWS was performed by Malcolm et al [27]; it showed equal effectiveness in detoxification along with some distinct advantages over lorazepam in the early post-detoxification period (described in more detail in Sect.…”
Section: Non-benzodiazepine Anticonvulsants (Nbacs) For the Treatmementioning
confidence: 99%
“…The improved anticonvulsant activity exhibited by BIA 2-093 compared to that of OXC suggests that the former is not just a precursor of active metabolite MHD, but a drug in its own right [48]. The in vivo mode of action of this analogue [50][51], toxicity profile [52] and applications in the treatment of CNS disorders are currently being investigated [53]. Additionally, the same researchers also prepared 10-hydroxylimino derivative 80, named BIA 2-024, upon condensation of OXC with hydroxylamine hydrochloride, which exhibited similar anticonvulsant profile to that of OXC [54].…”
Section: Type Ii: Analogues Obtained Through Modification On the 10-kmentioning
confidence: 99%
“…Additionally, the same researchers also prepared 10-hydroxylimino derivative 80, named BIA 2-024, upon condensation of OXC with hydroxylamine hydrochloride, which exhibited similar anticonvulsant profile to that of OXC [54]. Nevertheless, the neurotoxicity profile [52], metabolism [51,55] and utility of analogue 80 in the treatment of CNS diseases is still under study (Fig. 3).…”
Section: Type Ii: Analogues Obtained Through Modification On the 10-kmentioning
confidence: 99%
“…The seven-membered ring 5H-dibenz[b,f]azepine nucleus (1) is a pharmaceutically important structure and constitutes the key subunit in tricyclic antidepressant drug substances such as carbamazepine (1a) and oxcarbazepine (1b) (Figure 1) [4]. These anticonvulsant and mood stabilizing drugs are primarily used for the treatment of epilepsy, bipolar disorder [5][6][7], trigeminal neuralgia [8], and other neurological disorders [9]. Sulphonamides represent an important class of medicinally important molecules and are known to possess wide varieties of biological activities, hence sulphonamides moieties are an integral part of many antimicrobial drugs, saluretics, carbonic anhydrase inhibitors, antithyroid agents, antitumour drugs, etc.…”
Section: Introductionmentioning
confidence: 99%